Indonesia: Coping with economic and political instability - Fuglie, Keith O.; Piggott, Roley R. (International Food Policy Research Institute, 2006)
Indonesia is a Southeast Asian archipelago consisting of some 17,500 equatorial islands (6,000 of which are inhabited) stretching in an east–west direction over 5,000 kilometers. It has a land area of 1.83 million square kilometers; in 2000 this supported a population of 203.5 million (the fourth largest in the world), which is growing at about 1.4 percent per annum. While the overall population density is about 111 persons per square kilometer, 59 percent of the population lives on the island of Java, which has a population density of 944 persons per square kilometer. The overall ratio of urban to rural population was about 40:60 in 1999 (22:78 in 1980).